2014
DOI: 10.1089/scd.2013.0424
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-Induced Early Growth Response Protein-1 Binding to SNAIL Promoter in Epithelial–Mesenchymal Transition of Human Embryonic Stem Cells

Abstract: Epithelial-mesenchymal transition (EMT) has been thought to occur during early embryogenesis, and also the differentiation process of human embryonic stem (hES) cells. Spontaneous differentiation is sometimes observed at the peripheral of the hES cell colonies in conventional culture conditions, indicating that EMT occurs in hES cell culture. However, the triggering mechanism of EMT is not yet fully understood. The balance between self-renewal and differentiation of human pluripotent stem (hPS) cells is contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…The EMT process has been described under various hESC differentiation conditions, and its association with the differentiation of hESCs has also been confirmed . EMT of hESCs involves the E‐to‐M morphological conversion and marker expression change.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The EMT process has been described under various hESC differentiation conditions, and its association with the differentiation of hESCs has also been confirmed . EMT of hESCs involves the E‐to‐M morphological conversion and marker expression change.…”
Section: Discussionmentioning
confidence: 84%
“…While we demonstrated that WNT5A contributes to in vitro differentiation of hESCs, the precise route by which WNT5A regulates hESC differentiation remains to be defined. Our results raise two possibilities: (i) WNT5A may directly target and down‐regulate the pluripotency regulatory circuit of hESC or (ii) it may directly activate differentiation pathways, such as the EMT pathway to augment the intensity of in vitro differentiation (Fig. ).…”
Section: Discussionmentioning
confidence: 91%
“…To define the relationship between JC‐1 intensity and cell differentiation status, H9 cells were stained with anti‐vimentin (an early differentiation maker [15, 20]) and anti‐OCT‐3/4 (a differentiation maker [13]). The JC‐1 signals were highly overlapped with those of vimentin (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunocytochemistry was performed as described previously [56,57]. The primary and secondary antibodies used in this study are listed in Supplementary Table S2.…”
Section: Methodsmentioning
confidence: 99%